Femur Fracture Associated with Knee Brace Wear in the Motocross Athlete: A Report of Two Cases and Review of the Literature - Amalie Erwood; Jacob M. Wilson; Andrew M. Schwartz; Mara L. Schenker; Thomas Moore (Case Reports in Orthopedics)
The sport of motocross entails off-road motorcycle racing and is associated with a high incidence of traumatic injury. While prophylactic knee braces are routinely worn, there has been anecdotal concern that brace use is linked to femoral shaft fractures. While this risk remains unreported in the medical literature, preventing this complication has played a role in new commercial knee brace designs. We present two cases in which two motocross riders sustained transverse femoral shaft fractures at the proximal portion of each respective knee brace. The fracture locations measured on anterior-posterior radiograph were 22 and 21.1 cm proximal to the center of the knee, which is also the recommended proximal extent of motocross knee braces. We propose that the rigid knee brace protects the ligamentous knee structures but may focus undue force on the proximal aspect of the brace. New knee brace designs have incorporated features to dissipate the potentially injurious force to prevent femur fracture. While knee braces undoubtedly help prevent ligamentous knee injury, these cases question the safety of standard brace design and highlight the need for further brace development to better protect the patient’s bony structures, in addition to the knee joint.